Pelatihan Yoga Asanas Untuk Menurunkan Stres Remaja di SMA dan SMK Negeri Kecamatan Sukawati, Kabupaten Gianyar Tahun 2019 - I Nengah sumirta; i made sukarja; i ketut labir; suratiah suratiah; surinati dewa ayu; luh putu yunianti SC; i gede wijanegara (Jurnal Pengabmas Masyarakat Sehat, 2020)
One problem that are very popular and often plagued. teenagers is stressThe problem of stress happened to teenagers are almost inevitable.Mentioned this time as a period “storm and pressure”, in most teenagers, hambatan-hambatan in their lives would be disturbing physical fitness and emotions, destroy motivation and the ability to success in school and destroy their personal relationships. One of the activities can solve the problems of youth it is doing yoga asanas .The purpose of this activity is to help reduce the stress experienced by young people in adapt to environmental niches. The results show pre test found most were being level ( 66 % ), and to post a test found there is a slight extent to which is as much as 68 people ( 68 % ) test results on the analysis found p value 0,000, there an effect training yoga asanas terhaap teenage stress level. Keywords: Remaja, Stres, Yoga Asanas.